PENGARUH UTANG LUAR NEGERI TERHADAP PEREKONOMIAN NASIONAL DALAM PRESPEKTIF EKONOMI SYARIAH - Zakiyah Zakiyah; Agus Purnomo (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2018)
The condition of Indonesia's economic development has been sustained by foreign loans, whose numbers have continued to increase from year to year. Various forms of programs and projects carried out by the Indonesian government to improve the welfare of the people also use sources of foreign loans. The inclusion of foreign or foreign debt loans makes the government obtain additional budget in carrying out economic development program activities in Indonesia, especially development programs in the form of education, health and economy. Foreign debt from 1997 to 2016 has increased due to the Indonesian state revenue budget not yet fulfilling the state budget from year to year which has resulted in the state making a proposal for foreign loans to meet the needs of increasing the economy of the community to achieve the country's welfare. This study uses a quantitative descriptive research approach. in order to find out the effect of foreign debt on the development of the Indonesian economy in a sharia economic perspective.